A phenomenological estimate of rescattering effects in $$B_s→ K^{*0}\bar{K}^{*0}$$ B s → K ∗ 0 K ¯ ∗ 0 - Yao Yu; Hai-Bing Fu; Han Zhang; Bai-Cian Ke (European Physical Journal C: Particles and Fields)
Abstract The measurements in $$b→ s$$ b → s penguin-dominated decays are widely recognized as a powerful test for searching for New Physics by studying the deviation from theoretical estimations within the Standard Model. We examine the final-state rescattering effects on the decay $$B_s→ K^{*0}\bar{K}^{*0}$$ B s → K ∗ 0 K ¯ ∗ 0 and provide estimations of the branching ratio and longitudinal polarization of $$B_s→ K^{*0}\bar{K}^{*0}$$ B s → K ∗ 0 K ¯ ∗ 0 , which is consistent with experimental observations. Our conclusion is that both short- and long-distance interactions contribute significantly in this decay. The small longitudinal polarization in $$B→ VV$$ B → V V modes may not be a signal for New Physics.